2021
DOI: 10.1051/e3sconf/202132403009
|View full text |Cite
|
Sign up to set email alerts
|

Carapace length-frequency distribution and carapace length-weight correlation of ornate spiny lobster (Panulirus ornatus) in Sebatik Island Waters – Indonesia

Abstract: Ornate spiny lobster (Panulirus ornatus) in Sebatik Island is a commercial fisheries commodity that has the highest price if we compare it with another lobster caught by the fisherman in Sebatik Island Waters. That causes the effort to catch this lobster to increase continuously. The availability of biological aspects data of ornate spiny lobster is needed as a basis for sustainable lobster resource management in Sebatik Island. This research aims to analyze the biological performance of ornate spiny lobster i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…Using the Von Bertalanffy model shown in Figure 8, the age at the first length catch (Lc) was 48 and 61 days. According to Muzammil and Kurniadi (2020) (Liu et al 2014). However, the male and female fish caught were 24.7-25.5 cm and 23.6-25.4 cm in length.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Using the Von Bertalanffy model shown in Figure 8, the age at the first length catch (Lc) was 48 and 61 days. According to Muzammil and Kurniadi (2020) (Liu et al 2014). However, the male and female fish caught were 24.7-25.5 cm and 23.6-25.4 cm in length.…”
Section: Discussionmentioning
confidence: 97%
“…Priyambodo et al (2020) reported that the lowest and highest catch seasons were from December to March and April to November, respectively. Research by Foo (2020) and Muzammil and Kurniadi (2020) reported an imbalance sex ratio between males and females. According to Mendes et al (2016), the asymptotic growth of the lobster carapace was inversely correlated with the growth rate.…”
Section: Discussionmentioning
confidence: 97%
“…Namun dengan adanya peningkatan akan kebutuhan manusia dan tekanan lingkungan yang menjadi habitat sumber daya hayati laut, mengakibatkan terjadinya banyak penurunan populasi dari biota perairan. Hal ini menyebabkan beberapa biota perairan seperti hiu (Balai Pengelolaan Sumberdaya Pesisir dan Lautan Direktorat Pengelolaan Ruang Laut [BPSPL], 2019; Suwelo, 2005), napoleon (Firdaus & Hafsaridewi, 2012;De Mitcheson et al, 2019), lobster mutiara (Muzammil & Kurniadi, 2021), dugong (BPSPL, 2015), dan penyu (Ario et al, 2016) menjadi langka dan terancam punah. Berdasarkan permasalahan tersebut, maka perlu dilakukan upaya konservasi meliputi aspek pelestarian, perlindungan, dan pemanfaatan.…”
Section: Pendahuluanunclassified